FIXING 'FIXED ASSETS' - Singer, Frank A. (The Accounting Review, 1957)
The definitions related to fixed assets are listed in descending order of frequency of usage. The first definition is by far the most frequent, appearing just over one-half of the time. The least frequent definition appeared a little less than ten per cent of the time. The differences here are differences in the scope of the fixed assets category, although every definition excludes those assets which would be classified as "current." The definitions tend either to set up categories for permanent investments or intangibles as separate from the current and fixed asset categories, or they tend to include one or both within the fixed asset group. No amount of any asset would be different under one fixed asset definition or another. The preparation of a balance sheet forces, in effect, the selection of one of the definitions. The income statement is unaffected by a choice of classifications. It is agreed that fixed assets include none of the items which should be classified as current assets.